Autoimmune Hemolytic Anemia in a Renal Transplant Patient Following Seasonal Influenza Vaccination - Imran Gani; George Hinnant; Rajan Kapoor; Natasha Savage (Case Reports in Hematology)
Vaccines aim to prevent disease occurrence, its severity, and resultant complications. Our patient, a 58-year-old male, received seasonal influenza vaccination as part of routine health maintenance. Three days later, he presented with malaise, fever, and yellowish discoloration of eyes. His labs showed hyperbilirubinemia, anemia, elevated lactate dehydrogenase, and low haptoglobin, consistent with hemolytic anemia. Autoimmune hemolytic anemia has been associated with vaccine use and may result from phenomena of molecular mimicry and cross-reactivity with the possible role of vaccine adjuvants as well. An underlying structural defect of the red blood cell membrane may make them prone to hemolysis. The differential diagnosis and work-up of hemolytic anemia is extensive, as performed in our case. Management strategies for vaccine-induced hemolysis may involve supportive care, red blood cell transfusion, steroids, and intravenous immunoglobulin.